How Does AI Support De-Identification of Medical Records? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2016)
The increasing digitization of medical records presents a dual-edged sword. On one hand, it offers unprecedented opportunities for medical research, enabling...
Keywords: Healthcare Data Privacy and Security; Support; De-Identification; Medical; Artificial Intelligence; Healthcare